Timely Communication Through Telehealth: Added Value for a Caregiver During COVID-19 - Hajjar, Lauren; Kragen, Ben (Frontiers in Public Health, 2021)
Objective: This caregiver case study applies the lens of relational coordination theory (RC) to examine the value of telehealth as a medium of care coordination for a pediatric patient with hypermobile Ehlers-Danlos Syndrome (hEDS) during the COVID-19 pandemic. Background: The COVID-19 pandemic has placed an unprecedented burden on the delivery of healthcare around the globe and has increased the reliance on telehealth services. Delivering telehealth requires a high level of communication and coordination within and across providers as well as between providers, patients and their families. However, it is less clear how telehealth impacts the coordination of care. In this paper, we provide insight into the quality of care coordination between providers and an informal caregiver following policy changes to the provider payment structure in Massachusetts. Methods: This paper employs a single-case, autoethnographic study design where one of the authors uses their experiential insights, as mother of the patient, to inform a wider cultural and political understanding of the shift to remote caregiving for a pediatric patient with hEDS. Data was collected using reflective journaling, interactive interviews, and participant observation and analyzed using content analysis. Results: Findings revealed four interrelating roles of the caregiver including, logistics support, boundary spanner, home health aide, and cultural translator. The adoption of telehealth was associated with improved timeliness and frequency of communication between the caregiver and providers. Findings about the impact of telehealth adoption on accuracy of communication were mixed. Mutual respect between the caregiver and providers remained unchanged during the study period. Conclusions: This paper highlights areas where payer policy may be modified to incentivize timely communication and improve coordination of care through telehealth services. Additional insight from the perspective of an informal caregiver of a patient with a rare chronic disease provides an understudied vantage to the care coordination process. We contribute to relational coordination theory by observing the ways that caregivers function as boundary spanners, and how this process was facilitated by the adoption of telehealth. Insights from this research will inform the development of telehealth workflows to engage caregivers in a way that adds value and strengthens relational coordination in the management of chronic disease.